2021
DOI: 10.1021/acschemneuro.1c00149
|View full text |Cite
|
Sign up to set email alerts
|

Kratom Alkaloids as Probes for Opioid Receptor Function: Pharmacological Characterization of Minor Indole and Oxindole Alkaloids from Kratom

Abstract: Dry leaves of kratom (mitragyna speciosa) are anecdotally consumed as pain relievers and antidotes against opioid withdrawal and alcohol use disorders. There are at least 54 alkaloids in kratom; however, investigations to date have focused around mitragynine, 7-hydroxy mitragynine (7OH), and mitragynine pseudoindoxyl (MP). Herein, we probe a few minor indole and oxindole based alkaloids, reporting the receptor affinity, Gprotein activity, and βarrestin-2 signaling of corynantheidine, corynoxine, corynoxine B, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 94 publications
1
19
0
Order By: Relevance
“…Over the past decade, kratom has been reported as a source for naturally occurring, G-protein–biased opioidergic alkaloids, and has been investigated for its effects on pain management ( Matsumoto et al, 2004 ; Kruegel et al, 2019 ; Chakraborty et al, 2021b ; Chakraborty and Majumdar, 2021 ), opioid withdrawal ( Wilson et al, 2020 , 2021 ), and alcohol abuse ( Gutridge et al, 2020 ) as well as its decreased reward profile relative to traditional opioids ( Hemby et al, 2019 ; Wilson et al, 2021 ). Here, we further probed the effects of kratom alkaloids and synthetic kratom alkaloid derivatives to obtain a better understanding of its in vivo pharmacology and in search of novel treatment options for alcohol use disorder.…”
Section: Discussionmentioning
confidence: 99%
“…Over the past decade, kratom has been reported as a source for naturally occurring, G-protein–biased opioidergic alkaloids, and has been investigated for its effects on pain management ( Matsumoto et al, 2004 ; Kruegel et al, 2019 ; Chakraborty et al, 2021b ; Chakraborty and Majumdar, 2021 ), opioid withdrawal ( Wilson et al, 2020 , 2021 ), and alcohol abuse ( Gutridge et al, 2020 ) as well as its decreased reward profile relative to traditional opioids ( Hemby et al, 2019 ; Wilson et al, 2021 ). Here, we further probed the effects of kratom alkaloids and synthetic kratom alkaloid derivatives to obtain a better understanding of its in vivo pharmacology and in search of novel treatment options for alcohol use disorder.…”
Section: Discussionmentioning
confidence: 99%
“…Recent literature is beginning to evaluate the pharmacological importance of the other major and minor alkaloids present in M. speciosa [15][16][17][18]. Investigation of the opioid and adrenergic binding affinities of five kratom alkaloids, including 2, 12, speciociliatine (15), corynantheidine, and 9-hydroxycorynantheidine, revealed that 15 exhibited stronger binding affinity to κand μopioid receptors than 12 [19]; interestingly, 12 and 15 only differ by their configuration at position C-3 [14].…”
mentioning
confidence: 99%
“…Meanwhile, absolute stereochemistry is found to be crucial in agonistic activity in the opioid receptor. In a recent report by Chakraborty et al (2021b) on the opioid receptor function of mitraciliatine (4), pharmacological evidence was reported on this phytoalkaloid. In this study, mitraciliatine (4) (K i (MOR): 135.1 ± 7.7 nM) portrayed partial opioid agonism and identified it as structurally unique natural products with safer, MOR-dependent antinociception.…”
Section: Pharmacology/structure Activity Relationship Study (Sars)mentioning
confidence: 99%